Multivariate Optimization for the Development of a Fast and Simple Ultrasound-Assisted Extraction Procedure for Multielemental Determination in Tea Leaves by Inductively Coupled Plasma Optical Emission Spectrometry (ICP OES) - Costa, Vinicius Camara; Guedes, Wesley Nascimento [UNESP]; Santos, Antonio de Santana [UNESP]; Nascimento, Madson Moreira (Springer, 2018)
The current study describes a fast and efficient procedure of ultrasound-assisted extraction for determination of Ca, Mg, K, Na, Cu, Zn, Mn, and Al in tea leaves by inductively coupled plasma optical emission spectrometry (ICP OES). The variables of procedure were optimized using the Box-Behnken design and the conditions selected were nitric acid concentration (1.0 mol L-1), sonication time (7 min), and sonication temperature (75 A degrees C). The extraction efficiency was calculated using the analyte concentration obtained by a total digestion procedure as reference. Accuracy was confirmed by analysis of certified reference material of apple leaves (NIST 1515) and spinach leaves (NIST 1570a) using the procedure proposed. A statistical evaluation using Student's t test showed that there is no significant difference between the value obtained with the proposed procedure and the certified value, at 95% confidence level. The proposed procedure was successfully applied and is a good alternative to conventional acid digestion procedure and can be applied to routine analysis for determination of Ca, Mg, K, Na, Zn, Mn, Cu, and Al in tea leaves used for the preparation of infusions.
Keywords: Tea leaves; Ultrasound-assisted extraction; Multivariate optimization; Box-Behnken design; ICP OES